Effect of Implementing a Designed Nursing Teaching Protocol on Nurse's Performance and Hemodialysis Patient outcomes - Ghada Hassan Ahmed Hassan ,; Hanan Abd El-Razik AbdEl-all,; Mohammad Abbas Sobh, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Hemodialysis is a life saving method   that can offer significant benefits for end stage renal diseases management, but it can have some serious complication if the patients didn't understand of its causes. The nurse plays a critical role in reducing complications of this method .This study aimed to assess nurse's performance regarding hemodialysis patients, design nursing teaching protocol for nurses working with hemodialysis patient, and evaluate the effect of implementing the designed teaching protocol on nurse's performance and patient outcomes. Research design:  A quasi-experimental research design was utilized in this study. Sample: Convenient sample of (35) nurses and (60) Adult patients who are receiving hemodialysis aged from (18 to 65) years from both sexes.  Setting: This study was conducted in the kidney dialysis unit at Assiut University Hospital. Tools:  three tools utilize for data collection were a) Pre/Post test questionnaire sheet for the nurses) b) Observation checklist sheet. c) Patient assessment sheet. Results:  Good improvement in the mean knowledge & practice scores were found after the implementing of designed teaching protocol.  In conclusion: Improving nurses' performances can affect in minimize   the incidence of hemodialysis complications. Recommendation: Provide written policy about the standardized nursing care that should be delivered to every patient in the unit.